70.5k views
4 votes
What is the sum of the geometric series?

What is the sum of the geometric series?-example-1
User Reda La
by
6.2k points

1 Answer

3 votes

Answer:

40

Explanation:

The given geometric series is:


\sum_(n=1)^4(-2)(-3)^(n-1).

When n=1,
a_1=(-2)(-3)^(1-1),
\implies a_1=(-2)(-3)^(0)=-2

When n=2,
a_2=(-2)(-3)^(2-1),
\implies a_2=(-2)(-3)^(1)=6

When n=3,
a_3=(-2)(-3)^(3-1),
\implies a_3=(-2)(-3)^(2)=-18

When n=4,
a_4=(-2)(-3)^(4-1),
\implies a_4=(-2)(-3)^(3)=54

The sum of the given series is:

-2+6-18+54=40

User Piotr Tomasik
by
5.8k points